Enamel Pearls Implications on Periodontal Disease - Elton Gonçalves Zenóbio; Thaís Ribeiral Vieira; Roberta Paula Colen Bustamante; Hayder Egg Gomes; Jamil Awad Shibli; Rodrigo Villamarin Soares (Case Reports in Dentistry)
Dental anatomy is quite complex and diverse factors must be taken into account in its analysis. Teeth with anatomical variations present an increase in the rate of severity periodontal tissue destruction and therefore a higher risk of developing periodontal disease. In this context, this paper reviews the literature regarding enamel pearls and their implications in the development of severe localized periodontal disease as well as in the prognosis of periodontal therapy. Radiographic examination of a patient complaining of pain in the right side of the mandible revealed the presence of a radiopaque structure around the cervical region of lower right first premolar. Periodontal examination revealed extensive bone loss since probing depths ranged from 7.0 mm to 9.0 mm and additionally intense bleeding and suppuration. Surgical exploration detected the presence of an enamel pearl, which was removed. Assessment of the remaining supporting tissues led to the extraction of tooth 44. Local factors such as enamel pearls can lead to inadequate removal of the subgingival biofilm, thus favoring the establishment and progression of periodontal diseases.